The effects of health education on health science teachers' intention to recommend adolescent HPV vaccine for female students in Japan - Naruhiko Ishiwada; Chieri Suzuki; Sana Hasebe; Ayako Tsuchiya; Noriko Takeuchi; Haruka Hishiki; Yasunori Sato; Katsuo Sugita (Taylor & Francis Group, 2020)
The Japanese government suspended proactive recommendation of human papillomavirus (HPV) vaccination due to several reports of adverse events related to it in 2013. After that, the immunization rate of HPV vaccine quickly declined in Japan. Health science teachers (HSTs) are qualified and licensed teachers in charge of health care and health education for students in Japanese schools. HSTs have not recommended HPV vaccination to female students, since active governmental recommendation for HPV vaccination was halted for 5 y. We conducted a primary survey targeting HSTs (N = 39) and university students taking the HST training course (N = 123). In each group, awareness regarding HPV vaccine and disease burden was evaluated and factors related to and barriers to HPV vaccine recommendation were identified. The primary survey found that many HSTs and university students recognized their insufficient knowledge regarding the HPV vaccine. Based on the primary survey's results, infectious disease specialists, collaborating with Japanese HSTs, developed educational slide sets on HPV vaccine. A secondary survey was conducted before and after the lecture with HSTs (N = 162), where we evaluated their intelligibility and intention to recommend HPV vaccination for female students. In the post-lecture, secondary survey, the number of HSTs who recommended the HPV vaccine to their students had statistically increased from 76 before the lecture, to 103 (p < .05). An educational lecture using appropriate materials improved HSTs' vaccine confidence and intention to recommend the HPV vaccine to their students, verifying the study's hypothesis.